Role of scaffold network in controlling strain and functionalities of nanocomposite films - Chen, Aiping (Sci Adv, 2016)
Strain is a novel approach to manipulating functionalities in correlated complex oxides. However, significant epitaxial strain can only be achieved in ultrathin layers. We show that, under direct lattice matching framework, large and uniform vertical strain up to 2% can be achieved to significantly modify the magnetic anisotropy, magnetism, and magnetotransport properties in heteroepitaxial nanoscaffold films, over a few hundred nanometers in thickness. Comprehensive designing principles of large vertical strain have been proposed. Phase-field simulations not only reveal the strain distribution but also suggest that the ultimate strain is related to the vertical interfacial area and interfacial dislocation density. By changing the nanoscaffold density and dimension, the strain and the magnetic properties can be tuned. The established correlation among the vertical interface—strain—properties in nanoscaffold films can consequently be used to tune other functionalities in a broad range of complex oxide films far beyond critical thickness.